Fatigue behaviors of square-to-square hollow section T-joint with corner crack II : numerical modeling - Lee, Chi King (2014)
Based on the experimental results obtained in the first part of the study, a geometrical model and a mesh generation procedure are suggested for the numerical modeling of the uncracked and cracked square-to-square hollow section (SSHS) T-joints. In the proposed model, the surface crack is represented as an unsymmetrical 3D curved surface with the deepest point located at the corner of the brace-chord intersection. The mesh generation scheme developed is capable to generate well graded finite element (FE) meshes for cracked SSHS T-joints with multiple cracks. The validity of the proposed geometrical model and the reliability of the proposed mesh generation scheme are checked by comparing the predicted SIFs and the residual life against those computed based on the actual measurements. It is found that the suggested modeling method is reliable in the sense that conservative predictions for the SIFs and the residual life are obtained from the numerical simulations.